Experiências de mobilidade: o uso de aplicativos de ônibus na cidade de São Paulo - Rodilha, Bruno Grandchamp (2020)
The smartphones’ popularization and the GPS (Global Positioning System) technological advances have driven digitally intermediated daily practices of the major cities inhabitants. One of these activities is the commuting, which has found support in Location Based Services (LBS) applications for information and guidance. From this scenario, the present research focuses on the use of these apps, with special attention to the relationships between people, urban landscape and digital systems, in order to grasp the experiential aspects involved in these dynamics. Therefore, it was decided to observe the question by the bus service, due to its importance for the urban mobility in the city of São Paulo. Thus, the dissertation develops in three moments: firstly it is dedicated to the contextualization and problematization of the city, its displacements and information; next, the dissertation turns to a conceptual discussion about design practice and the interfaces; and finally, an exposition and interpretation of the use experience of two applications (Google Maps and Moovit). Thereby, it’s intended to document the current urban and technological mobility scenario, and to contribute to the design field through a phenomenological approach